2018
DOI: 10.1177/1687814018815271
|View full text |Cite
|
Sign up to set email alerts
|

A novel sliding mode single-loop speed control method based on disturbance observer for permanent magnet synchronous motor drives

Abstract: A novel speed control method based on sliding mode control and disturbance observer is studied for permanent magnet synchronous motor drives. Different from the conventional speed and current cascade control structure in the fieldoriented vector control, the new controller adopts the single-loop control structure, in which the speed and quadrate axes current controllers are combined together. First, a multiple-surface sliding mode controller is designed for the speed control system of permanent magnet synchron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…When L d = L q is satisfied, the motion equation of PMSM is given as: 42…”
Section: Problem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…When L d = L q is satisfied, the motion equation of PMSM is given as: 42…”
Section: Problem Descriptionmentioning
confidence: 99%
“…where T e is the electromagnetic torque; f f presents the flux of permanent magnet; L d ,L q ,i d (t) and i q (t) present inductance components and current components of the dqÀ axes. When L d = L q is satisfied, the motion equation of PMSM is given as: 42 T e À T L = J dv(t) dt + Bv(t),…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The basic principle of DOB is that the difference between the output of the actual model and the reference model caused by the external disturbance of the controlled object and its parameter changes, is regarded as the system disturbance. DOB estimates the output difference caused by the disturbance in real time and feedforward compensates it to the input, so as to actively suppress the influence of the disturbance [25]. Its control structure is in Figure 5.…”
Section: Control Algorithm Of a Photovoltaic And Energy Storage Systemmentioning
confidence: 99%
“…Ming et al 9 used an adaptive law-based PI control method to control the motor speed based on the study of model reference adaptive system (MRAS) sensorless control. Liu et al 10 studied a new speed control method based on sliding mode control and disturbance observer for a permanent magnet synchronous motor drive system. It is also demonstrated that the designed controller has a fast transient response and robustness under different operating conditions.…”
Section: Introductionmentioning
confidence: 99%